Do vascular risk factors contribute to the prevalence of pressure ulcer in veterans with spinal cord injury? - Rabadi, Meheroz Hoshang (Maney Publishing, 2011)
OBJECTIVE: The overall goal of this observational study was to determine whether modifiable vascular risk factors contribute to the prevalence of pressure ulcers (PrU) in veterans with traumatic spinal cord injury (SCI). BACKGROUND: Given the increasingly limited financial resources in hospitals and clinics, identifying risk factors associated with the development of PrU in persons with SCI will be a major step in reducing the cost of care for these individuals, and may improve their quality of life. METHOD: We retrospectively reviewed the electronic charts of 87 veterans with SCI who are being followed regularly in our SCI clinic and are enrolled in the SCI registry. The data collected included the basic demographics, presence of modifiable vascular risk factors such as hypertension, diabetes mellitus, hyperlipidemia, and current smoking; presence of incontinence and depression; and results from blood drawn for hemoglobin level, blood urea nitrogen, creatinine, and albumin levels and lipid profile on veteran's initial enrollment. Local Institution Review Board approval was obtained for the protocol. RESULTS: Of the 87 veterans with SCI, 27 had PrU. Comparisons between those with and without PrU found no significant differences for the demographic variables of age, gender, age of SCI onset, or SCI duration, but there was a trend for the groups to differ in ethnicity (P = 0.05). Similarly, the presence of modifiable vascular risk factors including hypertension, diabetes mellitus, hyperlipidemia, and current smoking did not differ between those with and without PrU. There were 36 pressure ulcer sites observed in 27 people. The proportion of pressure ulcer sites (of the 36) significantly differed by SCI severity based on the American Spinal Injury Association (ASIA) score (P < 0.0001). CONCLUSION: This study suggests that the presence of PrU was influenced by the severity of the SCI without any contribution from modifiable vascular risk factors.